Euthanasia in the European Union: Legal Diversity, Ethical Dilemmas, and the Quest for Harmonized Standards - Amna Warsi; Dr. Tansif Ur Rehman; Sarmad Ijaz (Indus Journal of Social Sciences, 2025)
Euthanasia, or intentional end-of-life to relieve pain, is a debatable legal and moral topic in the European Union (EU). The member states have different strategies influenced by cultural values, constitutional principles, and human rights frameworks. Other European countries that have legalized active euthanasia, in very strict conditions and within strict guidelines, are the Netherlands, Belgium, and Luxembourg, which focus more on patient autonomy, medical control, and informed consent. Conversely, other countries, such as Poland, Ireland, and Malta, outlaw any euthanasia, with religious and moral reasons. In other countries such as Germany and Spain, changing legal reforms and constitutional court decisions have seen the scales of individual rights and ethical issues being balanced. The European Court of Human Rights (ECHR) is relevant since it interprets Article 2 (right to life) and Article 8 (right to private life) of the European Convention on Human Rights, which indirectly affects the national laws. This paper analyses legal frameworks of euthanasia in the EU with a critical analysis of differences, problems, and possibilities of having harmonized ethical standards.